2015
DOI: 10.1080/08964289.2015.1086721
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in Migraine with Functional Somatic Syndromes, Psychiatric Disorders and Inflammatory Diseases: A Matter of Central Sensitization?

Abstract: To approach the questions as to why migraine appears to be associated with functional somatic syndromes (FSSs) and whether central sensitization may be an underlying mechanism, the present study investigated (a) comorbidity with diagnoses of three FSSs, three psychiatric disorders, and three inflammatory diseases, (b) degree of mental health problems (stress, burnout, anxiety, depression and somatization), and (c) prevalence of ten cognitive/affective and nine airway symptoms in persons with migraine in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Although no other study has applied neuroimaging to characterize FM in a coexisting disorder, dysfunctional DMN–insula functional connectivity has been observed in irritable bowel syndrome , chronic back pain , and migraine , all of which are pain conditions in which central sensitization has been implicated . Interestingly, these conditions are also associated with somatic symptoms , which is consistent with our post hoc analysis indicating that the DMN–insula functional connection relates not only to pain but also to symptoms such as fatigue and cognitive dysfunction (as measured by the Symptom Severity Index ). One notable discrepancy with previous non‐RA studies is the absence of a correlation with current pain severity (which we have further confirmed with a voxelwise search of the insula).…”
Section: Discussionsupporting
confidence: 86%
“…Although no other study has applied neuroimaging to characterize FM in a coexisting disorder, dysfunctional DMN–insula functional connectivity has been observed in irritable bowel syndrome , chronic back pain , and migraine , all of which are pain conditions in which central sensitization has been implicated . Interestingly, these conditions are also associated with somatic symptoms , which is consistent with our post hoc analysis indicating that the DMN–insula functional connection relates not only to pain but also to symptoms such as fatigue and cognitive dysfunction (as measured by the Symptom Severity Index ). One notable discrepancy with previous non‐RA studies is the absence of a correlation with current pain severity (which we have further confirmed with a voxelwise search of the insula).…”
Section: Discussionsupporting
confidence: 86%
“…The present study included only patients with episodic migraine to ensure a more homogeneous study group, given that there are important pathophysiological and clinical differences between episodic and chronic migraine 20 . It has been reported that migraine is often accompanied by such functional somatic syndromes as fibromyalgia, irritable bowel syndrome, chronic fatigue syndrome and back pain 9,22 . The authors attribute this to the common pathophysiological mechanism of central sensitization, and the increased SSA among migraine patients in the present study can be regarded as a reflection of this.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have observed increased depression and anxiety in patients who also report migraine [65][66][67][68], and there is evidence to support that anxiety and/or depression may be impacted by increasing headache frequency [66]. In an outpatient psychiatric clinic setting, patients with major depression were followed in a longitudinal manner for 10 years [69].…”
Section: Psychiatric and Sleep Conditionsmentioning
confidence: 99%